Cognitive behaviour therapy complemented with emotion regulation training for patients with persistent physical symptoms: a randomised clinical trial - Kleinstäuber, Maria; Bailer, Josef (Psychotherapy and psychosomatics, 2019)
Introduction: Persistent medically unexplained symptoms (MUS) are a major burden for health care. Cognitive behaviour therapy (CBT) is efficacious for patients with MUS, with small to medium effects. The current study investigates whether therapy outcomes of a CBT for MUS patients can be improved by complementing it with emotion regulation training. Methods: In a multicentre trial 255 patients with at least three persisting MUS were randomised to 20 sessions of either conventional CBT (n = 128) or CBT complemented with emotion regulation training (ENCERT; n = 127). Somatic symptom severity and secondary outcomes were assessed at pre-treatment, therapy session 8, end of therapy, and 6-month follow-up. Results: Linear mixed-effect models revealed medium to large effects in both study arms for almost all outcomes at the end of therapy and 6-month follow-up. ENCERT and CBT did not differ in their effect on the primary outcome (d = 0.20, 95% CI: -0.04 to 0.44). Significant time × group cross-level interactions suggested ENCERT to be of more benefit than conventional CBT for a few secondary outcomes. Moderator analyses revealed higher effects of ENCERT in patients with co-morbid mental disorders. Discussion/Conclusions: Current findings are based on a representative sample. Results demonstrate that both CBT and ENCERT can achieve strong effects on primary and secondary outcomes in MUS patients. Our results do not indicate that adding a training in emotion regulation skills generally improves the effect of CBT across all patients with MUS. Large effect sizes of both treatments and potential specific benefits of ENCERT for patients with co-morbid mental disorders are discussed.
Gesehen am 31.10.2019